Kajian transpor kreatinin menggunakan membran kitosan-alginat tertaut silang polivinil alkohol (PVA) - Ni Putu Sri Ayuni; Ni Wayan Yuningrat; Ni Wayan Citra (Jurnal Rekayasa Proses, 2018)
The objective of this research was to determine the efficiency of the creatinine transport using chitosan alginate cross linked by polyvinyl alcohol (PVA) 0.1% with 70, 100, and 130 mg/L of creatinine concentration. The subject of this study was the membranes of chitosan alginate PVA, while the object of this study was the efficiency of the creatinine transport. The PVA 0.1% cross-linking chitosan-alginate membrane (1:0.15) was successfully synthesized. The membrane synthesized was characterized by FTIR, as well as tensile and strain test. The FTIR spectra showed that there is a new peak of the amino group of chitosan and carboxyl group of alginate at ca. 1651 cm-1. The hydroxyl group appears at ca. 1088 cm-1 while ester groups at ca. 1088 cm-1 and ca. 1265 cm-1 which indicate the cross binding between alginate and PVA. The water uptake test of the chitosan alginate PVA membrane reaches 257.76% for 6 hours. The tensile test results of the membrane before and after creatinine transport are 2.77 MPa and 12.56 MPa while the strain tests yield 14.24% and 18.51%, respectively. The maximum efficiency of the creatinine transport using the chitosan-alginate cross linked by PVA is 51.02% at 130 mg/L creatinine. This creatinine transport result using the PVA cross linking chitosan-alginate membrane are more efficient than chitosan-pectin membrane (25.24%) with the same creatinine concentration.